2020
DOI: 10.1016/j.jcv.2020.104483
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing from extraction-free direct PCR of dried serum spots for portable hepatitis B virus drug-resistance typing

Abstract: Background: Effective drug regimens for the treatment of hepatitis B virus (HBV) infections are essential to achieve the World Health Organisation commitment to eliminate viral hepatitis by 2030. Lamivudine (3TC) is widely used in countries with high levels of chronic HBV, however resistance has been shown to occur in up to 50% of individuals receiving continuous monotherapy for 4 years. Telbivudine (LdT) is now more commonly used in place of lamivudine but is ineffective against 3TC-resistant HBV. Genotyping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Astbury et al 5 conducted the only HBV study in the region of Sao Jose do Rio Preto, and identified the subgenotypes A1, A2, B1, D1, D2, D3, F1 and F2. In the present study, we detected the same subgenotypes but we collected a larger number of samples in a much larger area of the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astbury et al 5 conducted the only HBV study in the region of Sao Jose do Rio Preto, and identified the subgenotypes A1, A2, B1, D1, D2, D3, F1 and F2. In the present study, we detected the same subgenotypes but we collected a larger number of samples in a much larger area of the region.…”
Section: Discussionmentioning
confidence: 99%
“…Astbury et al 5 conducted the only study of HBV genotyping and resistance mutations analysis in Sao Jose do Rio Preto. They identified the subgenotypes A1, A2, B1, D1, D2, D3, F1 and F2, in addition to strains resistant to the nucleoside analogues (NA) lamivudine (LAM), entecavir (ETV), and telbivudine (LDT).…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-long reads are more likely to cover the complete viral genome, highly repetitive regions, and structural variations in human genome, allowing continuous and complete genome assembly ( Jain et al, 2018 ; Senol Cali et al, 2018 ). With their long reading capacity, nanopore sequencing technologies have shown great advantages in the rapid surveillance of Ebola ( Hoenen, 2016 ; Quick et al, 2016 ) and Zika viruses ( Quick et al, 2017 ), genotyping and genetic diversity analysis of hepatitis B virus (HBV) ( Sauvage et al, 2018 ; McNaughton et al, 2019 ; Astbury et al, 2020 ), and monitoring emerging infectious disease outbreaks ( Zhu et al, 2020 ). Whole genome sequencing (WGS) of SARS-CoV-2 with nanopore sequencing technologies provided a unique tool to analyze viral transmission, evolution, and genomic variation ( Bull et al, 2020 ; Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of next-generation sequencing (NGS) techniques has considerably improved the detection and characterization of microbial and viral genetic sequences. Although initially used to study environmental, animal, and human samples, NGS has been more recently introduced in clinical microbiology and virology laboratories [ 1 5 ]. Its technical requirements, processing time, and cost are now compatible with diagnostic use.…”
mentioning
confidence: 99%
“…We report for the first time, to the best of our knowledge, the concurrent detection and determination of HBV and HDV sequences, including full HBV genome recovery, on the same day and directly from nucleic acids extracted from plasma. Illumina or ONT NGS has been previously used to obtain HBV or HDV sequences, but generally only after target enrichment, which is more time-consuming [ 2 , 9 ]. NGS directly from DNA or RNA extract without PCR amplification, as was done in the present case, is simpler and faster and allows simultaneous detection of several non-targeted infectious agents.…”
mentioning
confidence: 99%